Initial teacher preparation program in Saudi Arabia: history and framework for transformation toward a new era - Alharbi, Mashael S.; Albidewi, Ibrahim A. (Frontiers in Education, 2024)
Teacher quality is one of the most significant factors influencing the overall effectiveness of an education system. In this process, educators emphasize that teachers play the most crucial role in the educational process. Highlighting the importance of teachers draws attention to the value of their education, training, and readiness. This article discusses the history of initial teacher preparation (ITP) and its development within the context of Saudi Arabia. Drawing on the relevant literature, this review paper explores the fundamental elements that (ITP) education should include to achieve Vision 2030 goals for preparing future teachers. The paper also provides a proposed organizational framework for initial teacher preparation (ITP) in Saudi Arabia. The point in focusing on this topic lies in its academic contribution to the background context of initial teacher preparation (ITP), where little research has been published over the past years.